2018
DOI: 10.18632/oncotarget.24878
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of the EMSY gene expression and polymorphisms in ovarian cancer

Abstract: EMSY, a BRCA2–associated protein, is amplified and overexpressed in various sporadic cancers. This is the first study assessing the clinical impact of its expression and polymorphisms on ovarian cancer (OvCa) outcome in the context of the chemotherapy regimen used. In 134 frozen OvCa samples, we assessed EMSY mRNA expression with Reverse Transcription-quantitative PCR, and also investigated the EMSY gene sequence using SSCP and/or PCR-sequencing. Clinical relevance of changes in EMSY mRNA expression and DNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Considering the vast biological diversity of highgrade ovarian cancers, resulting in many apparently discrepant results, as clearly demonstrated herein in the discussion section, the discovery of universal, cohort-independent biomarkers is of paramount importance. As we have shown in our previous research on the CEBPA [2] and EMSY [3] genes, both expression changes and genetic alterations may affect ovarian cancer prognosis and/or response to chemotherapy. The clinical impact of such changes can also be mutually dependent, as observed for example in a nonsense-mediated mRNA decay (NMD), a gene regulatory mechanism which results in low concentrations of mRNAs transcribed from alleles carrying nonsense mutations [4].…”
Section: Introductionmentioning
confidence: 76%
“…Considering the vast biological diversity of highgrade ovarian cancers, resulting in many apparently discrepant results, as clearly demonstrated herein in the discussion section, the discovery of universal, cohort-independent biomarkers is of paramount importance. As we have shown in our previous research on the CEBPA [2] and EMSY [3] genes, both expression changes and genetic alterations may affect ovarian cancer prognosis and/or response to chemotherapy. The clinical impact of such changes can also be mutually dependent, as observed for example in a nonsense-mediated mRNA decay (NMD), a gene regulatory mechanism which results in low concentrations of mRNAs transcribed from alleles carrying nonsense mutations [4].…”
Section: Introductionmentioning
confidence: 76%
“…However, this may only be the case when EMSY is coamplified with CCND1 , at least for patients with estrogen receptor–positive breast cancer . In patients with OC, EMSY amplification and messenger RNA (mRNA) overexpression has been previously reported in association with worse survival . However, Hollis et al reported that high EMSY expression was associated with prolonged survival and greater platinum sensitivity in a cohort of 265 high‐grade serous epithelial OC from Edinburgh, as well as multiple publicly available datasets …”
Section: Amplification and Overexpressionmentioning
confidence: 99%
“…11 In patients with OC, EMSY amplification and messenger RNA (mRNA) overexpression has been previously reported in association with worse survival. 7,12 However, Hollis et al reported that high EMSY expression was associated with prolonged survival and greater platinum sensitivity in a cohort of 265 highgrade serous epithelial OC from Edinburgh, as well as multiple publicly available datasets. 13 Amplification of the EMSY gene in OC and other cancer types has been reported to correlate with EMSY mRNA expression in multiple studies, 1,3,4,8 whereas reports regarding the association between EMSY mRNA and protein expression have been limited and conflicting.…”
mentioning
confidence: 99%
“…Effects and mechanisms of genetic, epigenetic, and chemical perturbations on cellular viability are explored in vitro and in vivo through gene knockdown, knockout, and transfection assays using human cell lines (4)(5)(6)(7). Cellular assays employing human cell lines have proven essential to determine the impact of intra-and intergenetic polymorphisms on gene expression and cellular viability (8,9). Although impactful mutations altering gene expression, cell function, or cell viability have been observed, there is significant variability in reproducibility among varying cell lines (10,11).…”
Section: Introductionmentioning
confidence: 99%